User Modeling, Adaptation and Personalization 23rd International Conference, UMAP 2015, Dublin, Ireland, June 29 -- July 3, 2015. Proceedings - Ricci, Francesco; Bontcheva, Kalina; Conlan, Owen; Lawless, Séamus (Information Systems and Applications, incl. Internet/Web, and HCI, 2015)
This book constitutes the refereed proceedings of the 23rd International Conference on User Modeling, Adaptation and Personalization, UMAP 2015, held in Dublin, Ireland, in June/July 2015. The 25 long and 7 short papers of the research paper track were carefully reviewed and selected from 112 submissions. The papers reflect the conference theme "Contextualizing the World", highlighting the significance and impact of user modeling and adaptive technologies on a large number of everyday application areas such as: intelligent learning environments, recommender systems, e-commerce, advertising, personalized information retrieval and access, digital humanities, e-government, cultural heritage, and personalized health.